Controlled Hydrophobic Functionalization of Natural Fibers through Self‐Assembly of Amphiphilic Diblock Copolymer Micelles. Issue 7 (17th May 2013) - Aarne, Niko; Laine, Janne; Hänninen, Tuomas; Rantanen, Ville; Seitsonen, Jani; Ruokolainen, Janne; Kontturi, Eero
Abstract The functionalization of natural fibers is an important task that has recently received considerable attention. We investigated the formation of a hydrophobic layer from amphiphilic diblock copolymer micelles [polystyrene‐block‐poly(N‐methyl‐4‐vinyl pyridinium iodide)] on natural fibers and on a model surface (mica). A series of micelles were prepared. The micelles were characterized by using cryoscopic TEM and light scattering, and their hydrophobization capability was studied through contact angle measurements, water adsorption, and Raman imaging. Mild heat treatment (130 °C) was used to increase the hydrophobization capability of the micelles. The results showed that the micelles could not hydrophobize a model surface, but could render the natural fibers water repellent both with and without heat treatment. This effect was systematically studied by varying the composition of the constituent blocks. The results showed that the micelle size (and the molecular weight of the constituent diblock copolymers) was the most important parameter, whereas the cationic (hydrophilic) part played only a minor role. We hypothesized that the hydrophobization effect could be attributed to a combination of the micelle size and the shrinkage of the natural fibers upon drying. The shrinking caused the roughness to increase on the fiber surface, which resulted in a rearrangement of the self‐ assembled layer in the wet state. Consequently, the fibers became hydrophobic through the roughness effects at multiple length scales. Mild heat treatment melted the micelle core and decreased the minimum size necessary for hydrophobization.